Balancing Standardisation and Individualisation in Psychosocial Interventions for Perinatal Bereavement: Bereaved Parents' Perspectives From a Qualitative Study - Jiaying Xie; Annmarie Grealish; Linda Biesty; Andrew Hunter (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To explore bereaved parents' experiences of receiving psychosocial interventions (PSIs) in hospital‐based perinatal bereavement care in Ireland. Design Descriptive qualitative study. Methods Fifteen bereaved parents (13 mothers and 2 partners) whose loss occurred within the past three years were recruited via a national parent‐led charity. Semi‐structured online interviews were conducted between November 2024 and March 2025. Data were analysed using reflexive thematic analysis. Results Six themes captured parents' experiences: (1) emotional support as the foundation of feeling cared for; (2) informational support as essential for reassurance and preparedness; (3) practical and inclusive support to ease burdens and extend care; (4) memory‐making to reconstruct meaning and connection; (5) sustaining supports beyond hospital; and (6) contextual support for sensitivity, continuity, and consistency. Interpreting these themes through the Socio‐Ecological Model reflected multi‐level influences shaping parents' experiences of receiving PSIs during hospitalisation. Conclusion Key PSIs valued by parents included emotional, informational, practical, inclusive, memory‐making, psychological, and peer supports, as well as follow‐up and contextual sensitivity. However, variability in how these supports were offered revealed gaps between parents' expectations and practice. Implications for the Profession and/or Patient Care Findings highlight the need for a standardised framework outlining key PSIs, while retaining sufficient flexibility to accommodate individual preferences. Embedding these PSIs within organisational structures, supported by enhanced staff training, improved continuity of care, and minimisation of environmental triggers, has the potential to improve the quality, equity and consistency of perinatal bereavement care. Impact This study addresses gaps in understanding parents' perspectives on PSIs in perinatal bereavement care and offers practical insights to inform the development of core components of future PSIs for perinatal bereavement. Reporting Method COREQ. Patient or Public Contribution Bereaved parents and midwives formed a steering group, advising on study design, recruitment materials and interview guides, ensuring sensitivity and grounding in lived experience.